Economic evaluation of differentiated service delivery models for HIV treatment in Lesotho: costs to providers and patients. Issue 4 (10th April 2021) - Nichols, Brooke E; Cele, Refiloe; Lekodeba, Nkgomeleng; Tukei, Betty; Ngorima‐Mabhena, Nicoletta; Tiam, Appolinaire; Maotoe, Thapelo; Sejana, Makatleho Veronica; Faturiyele, Iyiola O; Chasela, Charles; Rosen, Sydney; Fatti, Geoffrey
Abstract: Introduction: Lesotho, the country with the second‐highest HIV/AIDS prevalence (23.6%) in the world, has made considerable progress towards achieving the "95‐95‐95" UNAIDS targets, but recent success in improving treatment access to all known HIV positive individuals has severely strained existing healthcare infrastructure, financial and human resources. Lesotho also faces the challenge of a largely rural population who incur a significant time and financial burden to visit healthcare facilities. Using data from a cluster‐randomized non‐inferiority trial conducted between August 2017 and July 2019, we evaluated costs to providers and costs to patients of community‐based differentiated models of multi‐month delivery of antiretroviral therapy (ART) in Lesotho. Methods: The trial of multi‐month dispensing compared 12‐month retention in care among three arms: conventional care, which required quarterly facility visits and ART dispensation (3MF); three‐month community adherence groups (CAGs) (3MC) and six‐month community ART distribution (6MCD). We first estimated the average total annual cost of providing HIV care and treatment followed by the total cost per patient retained 12 months after entry for each arm, using resource utilization data from the trial and local unit costs. We then estimated the average annual cost to patients in each arm with self‐reported questionnaire data. Results: The average total annual cost of providing HIV care and treatment per patient was the highest in the 3MF arm ($122.28, standard deviation [SD] $23.91), followed by 3MC ($114.20, SD $23.03) and the 6MCD arm ($112.58, SD $21.44). Per patient retained in care, the average provider cost was $125.99 (SD $24.64) in the 3MF arm and 6% to 8% less for the other two arms ($118.38, SD $23.87 and $118.83, SD $22.63 for the 3MC and 6MCD respectively). There was a large reduction in patient costs for both differentiated service delivery arms: from $44.42 (SD $12.06) annually in the 3MF arm to $16.34 (SD $5.11) annually in the 3MC (63% reduction) and $18.77 (SD $8.31) annually in 6MCD arm (58% reduction). Conclusions: Community‐based, multi‐month models of ART in Lesotho are likely to produce small cost savings to treatment providers and large savings to patients in Lesotho. Patient cost savings may support long‐term adherence and retention in care.